Metabolomic Profiling in Response to an Oral Glucose Tolerance Test Reveals Pathways Associated With Obesity and Insulin Resistance During the Pubertal Transition. (7th June 2021) - LaBarre, Jennifer; Hirschfeld, Emily; Iyer, Gayatri; Karnovsky, Alla; Herman, William; Peterson, Karen; Burant, Charles; Lee, Joyce
Abstract: Objectives: To reveal alterations in metabolic pathways in response to an oral glucose tolerance test (OGTT) underlying the development of insulin resistance during the pubertal transition. Methods: Participants were recruited as healthy controls (HC, n = 55, aged 8.3–18.0 years, BMI percentile 5–85%) and overweight and obese individuals (OVOB, n = 228, aged 8.1–17.9 years, BMI percentile ≥ 85%). Participants were grouped based on their peak insulin response to the OGTT, stratified by peak at t30 (Group 1, n = 163), t60 (Group 2, n = 75), and t120 minutes (Group 3, n = 44). Untargeted metabolomics profiled 267 annotated metabolites and > 3000 unannotated features in plasma at t0 and t60 minutes. Regression classified changes in metabolites across the time-course, assessing the influence of BMI and insulin response (FDR < 0.05). The connectivity of the metabolome was determined using differential network enrichment analysis (DNEA), stratified by insulin response group. Results: At fasting, 32% of the metabolites differed between HC and OVOB, including elevated kynurenine, leucine/isoleucine, methionine, tyrosine, short-chain acylcarnitines, and diacylglycerols in OVOB. At t60, only 4% of the metabolites differed between HC and OVOB participants, suggesting a "normalization" of the metabolome, with exceptions of acylcarnitines and FA oxidation (FAO) intermediates. Although no metabolites differed significantly between insulin response group, differential subnetworks were observed, including increased connectivity between FA and FAO intermediates in Group 1 at t60, suggesting differential regulation in post-prandial FAs. Conclusions: Profiling the metabolome response to an OGTT may highlight metabolic dysfunction prior to type 2 diabetes and will be used in future longitudinal analyses predicting insulin resistance trajectory. Funding Sources: The National Institute of Child Health and Human Development, the National Institute of Diabetes and Digestive and Kidney Diseases, and the National Institutes of Health